The Multi-Strain Probiotics Effect as Adjuvant Therapy for HIV Patients at Waluyo Jati Regional Hospital, Probolinggo Regency, East Java, Indonesia - Luki Harjanti; Adji Prayitno Setiadi; Nanik Triana Kartika (Malahayati Nursing Journal, 2026)
ABSTRACT Human Immunodeficiency Virus (HIV) infection causes Acquired Immune Deficiency Syndrome (AIDS) by attacking immune cells, especially T-helper lymphocytes (CD4). This study aims to determine the benefits of multi-strain probiotics as adjuvant therapy in People Live with HIV (PLHIV) with suppressed viral load at Waluyo Jati Regional Hospital with a primary focus on changes in CD4 levels and Opportunistic Infection. This study was conducted using the Quasi-Experimental Design One Group Pretest Posttest method involving 23 PLHIV at Waluyo Jati Regional Hospital. The sample individuals in this study were PLHIV with a history of suppressed viral load and had received ART (antiretroviral) therapy for at least 2 (two) years. Data collection in this study was carried out for 90 (ninety) days. Based on the Shapiro-Wilk normality test value, it is known that the research data obtained is data with a normal distribution (p 0.05). Based on this study, it was found that the administration of adjuvant therapy in the form of multi-strain probiotics show statistically significant effect on increasing CD4 levels in study participants after three months of treatment. Individually, 82,46 % of patients experienced an increase in CD4, while 17,36 % experienced a decrease in CD4 (p = 0.001; p 0.05). The supplementation of probiotics has a statistically significant effect on increasing CD4 cell levels in HIV patients undergoing antiretroviral (ART) therapy. The overall occurrence of opportunistic infections (OIs) in the study group was low throughout the three months observation period. Only two OI cases were identified, one case of pneumonia and one case of oral candidiasis. Both of which appeared in the first month, with no additional infections detected in the subsequent months. Keyword: HIV, Antiretroviral, Multi-strain Probiotic, CD4, Opportunistic Infections.